Influência da construção da hidrelétrica do rio Jordão sobre a ictiofauna : impactos e colonização. - Luiz, Elaine Antoniassi (2006)
Cap.1: Alterations prompted by the filling of Jordão Reservoir, located in the Jordão River, a tributary of the Iguaçu River, on the fish assemblage were evaluated. Captures were performed with gillnets (before and after reservoir filling; periods Pre, Pos 1 and Pos 2) with different mesh sizes. Four stations, previously selected considering the reservoir filling, were sampled. Abundance was indexed by catch per unit of effort (CPUE), that was used to evaluate spatial and temporal variations in demography, to measure some attributes (species richness, evenness and Shannon Diversity Index), and to describe composition and structure of fish assemblages as well (summarized in a detrended correspondence analysis - DCA). The endemism was considerable high (72.5% of the fish fauna). Most of the captured species was small to middle sized, mainly belonging to the orders Characiformes and Siluriformes. After the first year of filling (Pos 1), mean species richness increased in all sampling stations, with slightly lower values in the following year (Pos 2), except in the station located upstream from the reservoir. Evenness and Shannon Index decreased after reservoir filling. Composition and structure of the species varied among periods (Pre, Pos 1 and Pos 2), in all stations located above the dam. The most conspicuous change in the fish assemblage was verified in its structure (both spatial and temporal) instead in its composition (few species disappeared). Therefore, studies conducted before and after reservoir filling are fundamental, especially in low order rivers with high endemism. In addition, studies have to encompass adequate temporal and spatial scales, to allow a more precise identification of impacts resulted from reservoir filling.